Claudin-7 Inhibits Proliferation and Metastasis in Salivary Adenoid Cystic Carcinoma Through Wnt/β-Catenin Signaling. (30th July 2020) - Ji, Huan; Ding, Xu; Zhang, Wei; Zheng, Yang; Du, Hongming; Zheng, Yangyu; Song, Haiyang; Li, Meng; Jiang, Yue; Xie, Jiaxiang; Wu, Ming; Jiao, Pengfei; et al.
The aim of this study was to investigate claudin-7 (CLDN7) expression in salivary adenoid cystic carcinoma (SACC) and its function in SACC cells. We determined CLDN7 expression in SACC tumors via immunohistochemistry and western blotting and evaluated the association between CLDN7 expression and clinicopathologic variables. Besides this, we constructed a stably transfected CLDN7 knockdown SACC-LM cell line via RNAi and assessed its biological behavior changes (cell viability, migration, and invasion). The correlation between CLDN7 and epithelial-mesenchymal transition (EMT) was analyzed. Additionally, a subcutaneous tumor formation model was used to assess SACC-LM cells tumorigenicity after the CLDN7 knockdown. In the present study, we found the CLDN7 expression of tumor group was lower than that in normal salivary glands and was significantly correlated with lymph node metastasis, recurrence, and gender. CLDN7 knockdown could add the proliferation and metastasis ability of SACC by regulating EMT through Wnt/β-catenin signaling pathway. In addition, CLDN7 knockdown in SACC promoted tumor growth in nude mice. CLDN7 inhibits cell proliferation and metastasis by inactivating the Wnt/β-catenin signaling in SACC. Thus, CLDN7 expression might be a useful marker to identify the potential for progression in SACC.